Integrated Multi-Criteria Decision Making – Data Envelopment Analysis Models In Efficiency Analysis Of Sponsored Research - Khurizan, Noor Saifurina Nana (2018)
In the context of higher education administration, specifically for sponsored research, efficiency analysis has become an essential process for both sponsors and researchers. The evaluation process will provide the information on research productivity in fully utilising the resource to produce the desirable outcome. It is easier to evaluate the sponsored research’ performance when its efficiency is represented by a single score. Over the years, many methodologies have contributed into assessing the performance of sponsored research. Among the most popular ones are Multi-Criteria Decision Making (MCDM) Method and Data Envelopment Analysis (DEA). MCDM and DEA method both deal with problems concerning multiple inputs and outputs. This factor is crucial in efficiency analysis as most case studies are presented with more than one resource and outcome. The main objective of this study is to evaluate the efficiency of sponsored research in a university subject to its data availability and number of Decision Making Units (DMUs). The integrated MCDM-DEA methods are presented in order to fulfill the requirement of the main objective. The first case study presents a novel way of integrating three different MCDM and DEA model to evaluate the performance of a sponsored research from a much simpler form of data in a small size under the same grant. The integrated model has managed to handle the subjective data and objective data in producing the single score for each sponsored research.